Analysis of Wind Direction and Speed ??of Rainfall Distribution in Tangerang Regency - Clara Dwi Lestari Simbolon; Yayat Ruhiat; Asep Saefullah (Jurnal Teori dan Aplikasi Fisika, 2022)
The wind is the horizontal movement of air masses. Wind can occur if there is any difference in pressure between one place to another place. The pattern from the wind movement is the direction and velocity. That pattern becomes a part to influence the rainfall. This research is to determine the direction and velocity of wind who more dominant happens in the Tangerang district using a windrose method and to determine the relationship between the direction and velocity of wind to the distribution of rainfall with multiple linear regression analysis. This research uses secondary data which is daily data during the period of January 2011 to December 2020 and then the data will be processed using WRPLOT and Minitab software. Based on the results using the windrose method the data obtained that the direction of the wind is more dominant blows from the west to the east with an average wind speed of 2.93 m/s. Through the Kolmogorov-Smirnov test, the rainfall distribution test in the Tangerang district is normally distributed. The results of multiple linear regression show that wind has a negative effect on rainfall. The highest rainfall occurred in February 2020 as much as 556 mm with the wind blowing from the west-northwest.